Standardization of 5G new radio technology oriented Polar code - Desheng XIE; Rong CHAI; Leilei HUANG; Qianbin CHEN (Dianxin kexue)
Amore efficient new channel coding scheme was required for NRby the service features and capability indices of 5G.Due to its excellent performance,Polar code was specified as the control channel coding scheme for 5G enhancedmobile broadband(eMBB)scenario.An overview of Polar code was presented and themain existing research issues of the standardization for new radio(NR)technology oriented Polar code,including code construction,sequence design,rate-matching and channel interleaving,etc,were elaborated.Then some specific analysis and comparisons of the Polar code schemes which were proposed by 3GPPmember institutes in RAN1 conferences recently were presented.Finally,a summary of the standardization works of Polar code was given on the basis of the above discussions.